1999
DOI: 10.3109/10611869909085497
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Some Carboxylic Acids in the Olfactory System Following Intranasal Administration

Abstract: The uptake of [14C]benzoic acid, 4-chloro[14C]benzoic acid, [3H]phthalic acid and [14C]salicylic acid in the nasal passages and brain was determined following a unilateral intranasal instillation in mice. An uptake of radioactivity from the nasal mucosa to the ipsilateral olfactory bulb was observed up to 4 h after administration following intranasal instillation of these carboxylic acids whereas the level was low in the contralateral olfactory bulb. Autoradiography of mice given [14C]benzoic acid and [14C]sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It is reasonable to assume that molecules are able to utilise both transport pathways simultaneously. Eriksson et al have investigated the distribution of four carboxylic acids following intranasal administration (20). Autoradiography showed that the test substances were distributed throughout the olfactory nerve apparatus and the glomerular layer (outer layer) of the olfactory lobes at 0.5-4 h post-dose.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is reasonable to assume that molecules are able to utilise both transport pathways simultaneously. Eriksson et al have investigated the distribution of four carboxylic acids following intranasal administration (20). Autoradiography showed that the test substances were distributed throughout the olfactory nerve apparatus and the glomerular layer (outer layer) of the olfactory lobes at 0.5-4 h post-dose.…”
Section: Discussionmentioning
confidence: 98%
“…Dosing and subsequent sacrifice of each rat was staggered to allow prompt removal of the olfactory lobes and brain in a consistent manner. Blood samples (150-200 μl) were taken via the carotid cannula pre-dose and at 0 (immediately post-dose), 1, 2, 3,5,7,8,9,10,11,15,20,25 and 30 min post-dose.…”
Section: Quantitative Tissue Distributionmentioning
confidence: 99%
“…Also, lipopolysaccharides enhance the hepatoxicity of aflatoxin B1 in rats (Barton et al, 2001;Luyendyk et al, 2002Luyendyk et al, , 2003. Finally, C-14 aromatic carboxylic acids are transferred unchanged into the brain and olfactory bulbs following intranasal instillation in mice (Eriksson et al, 1999). These observations point towards at least one probable mechanism for the encephalopathy observed in humans exposed to the biocontaminants in damp indoor spaces.…”
Section: Mechanism Of Neurological Injurymentioning
confidence: 95%
“…To date, lot of work has been reported for brain targeting using intanasal route (Mathison et al, 1998;Stevens et al, 2011). Few of them include nerve growth factor (Chou & Donovan, 1998), inorganic mercury (Henriksson & Tjalve, 1998), dihydroergotamine (Wang et al, 1998), taurine (Brittebo & Eriksson, 1995), carboxylic acids (Eriksson et al, 1999), 2 0 ,3 0 -didehydro-3 0 -deoxythymidine (Yajima et al, 1998) and many high molecular weight peptides (Frey et al, 1997) bagged in INDD. Kumar et al (1982) who showed that progesterone (MW 314.46 Da) achieved a higher distribution in the CSF than in the blood after intranasal administration.…”
Section: Introductionmentioning
confidence: 99%